Co-Administration of Melatonin Effectively Enhances the Therapeutic Effects of Pioglitazone on Mesenchymal Stem Cells Undergoing Indoxyl Sulfate-Induced Senescence through Modulation of Cellular Prion Protein Expression - Yong Seok Han (International Journal of Molecular Sciences, 2018)
Background: Mesenchymal stem cells (MSCs) are a promising source for regenerative medicine. However, their therapeutic potential in patients with chronic kidney disease (CKD) is restricted by the presence of uremic toxins. To address this limitation, we explored the protective effect of melatonin and pioglitazone on MSCs undergoing senescence induced by the uremic toxin, indoxyl sulfate (IS). Methods: MSC senescence was induced by IS, and the therapeutic effects of melatonin and pioglitazone were identified. The expression of cellular prion protein (PrPC) was suppressed by transfection of MSCs with prion protein gene (PRNP) siRNA. Subsequently, these cells were used to study the protective effects of melatonin and pioglitazone against IS-induced senescence; Results: The IS-induced senescence of MSCs was significantly reduced by co-treatment with melatonin and pioglitazone compared to treatment with melatonin or pioglitazone alone. In the presence of IS, the reduced MSC proliferation was rescued by co-treatment with melatonin and pioglitazone. Melatonin and pioglitazone enhanced the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) in MSCs, which resulted in the augmentation of PrPC level. The inhibitory effect of the co-treatment with melatonin and pioglitazone on IS-induced senescence in MSCs was blocked by the knockdown of PRNP. In addition, the restorative effect of the co-treatment on the reduced MSC proliferation induced by IS was also blocked by the knockdown of PRNP. These findings indicate that co-treatment with melatonin and pioglitazone protected MSCs from uremic toxin-induced senescence through the regulation of the PPAR-γ-PrPC axis. Conclusions: Our study suggests that co-treatment of MSCs with melatonin and pioglitazone may represent a novel strategy for the development of MSC-based therapies for patients with CKD.